Protein, Magnesium and Phosphorous Intake at Stunted and Non-Stunted Children in Panularan Surakarta - Widiyaningsih, Endang Nur; Wahyuningtyas, Aulia Putri (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2017)
The first five years of children’s life are a very important period of growth and development because it will determine the success of children’s growth and development in the future. One of the nutritional problems occurs in children under five is stunting. We aimed to determine the mechanism of the inadequacy of protein, magnesium and phosphorus intake to stunting in children under five. This study involved 35 stunted children and 35 nonstunted children aged 12 to 60 months. The subjects were selected by simple random sampling technique. The data of protein, magnesium and phosphorus intake was obtained through 24-hour dietary recall in four times on nonconsecutive days. Most stunted and non-stunted children under five have a higher intake of protein, magnesium and phosphorus than the Recommended Daily Allowance. Average intake of protein, magnesium and phosphorus in non-stunted children are, respectively, 78.69 points, 124.57 points, and 117.04 points, which are higher than stunted children under five. There are differences in the adequacy of protein, magnesium and phosphorus intake in the stunted and non-stunted groups (p = 0.007, p = 0.011, and p = 0.003).